From 'merchants and ministers' to 'neutral brokers'? Water diplomacy aspirations by the Netherlands – a discourse analysis of the 2011 commissioned advisory report. Issue 6 (2nd November 2022) - Mukhtarov, Farhad; Gasper, Des; Alta, Aditya; Gautam, Neha; Duhita, Maria Sattwika; Hernández Morales, Diego
ABSTRACT: Water diplomacy agents typically manage tensions between promoting peace and securing self-interest. This paper conducts a discourse analysis of a commissioned policy report by a leading Netherlands think-tank that helped inform Dutch policy on water diplomacy. We first establish the importance of the report. We then identify its focus on the theme of 'neutral broker' and apply vocabulary analysis, argumentation analysis and metaphor analysis, together leading up to frame analysis. From this report and the larger water diplomacy literature, we propose that water diplomacy must be viewed in connection with discursive politics and trade promotion. We illustrate relevant methods for future enquiry.